Impact of perceived control on all-cause and cardiovascular disease mortality in three urban populations of Central and Eastern Europe: the HAPIEE study - Kozela, Magdalena; Pająk, Andrzej; Micek, Agnieszka; Besala, Agnieszka; Kubinova, Ruzena; Malyutina, Sofia; Tamosiunas, Abdonas; Pikhart, Hynek; Peasey, Anne; Nikitin, Yuri; Marmot, Michael; Bobak, Martin (Journal of epidemiology and community health, 2017)
BACKGROUND: Inverse associations between perceived control and cardiovascular disease (CVD) have been reported in studies from Western Europe and the USA. To assess this relationship across different populations, we investigated the association between perceived control and all-cause and CVD mortality in three population-based cohorts of Eastern European countries. METHODS: We analysed data from a prospective cohort study in random population samples in Krakow (Poland), Novosibirsk (Russia) and six Czech towns. Baseline survey included structured questionnaire and objective examination in a clinic. Perceived control was assessed using an 11-item scale developed by the MacArthur Foundation Programme on Successful Midlife. Information on vital status was obtained from death registers. Effect of perceived control on mortality was assessed using Cox proportional hazards models. RESULTS: A total of 2377 deaths (1003 from CVD) occurred among 27 249 participants over a median 7-year follow-up. In the Czech and Polish cohorts, perceived control was inversely associated with mortality; the adjusted HRs for the lowest versus highest control quintiles were 1.71 (1.34 to 2.19) in men and 1.63 (1.14 to 2.35) in women for all-cause mortality and 2.31 (1.48 to 3.59) and 5.50 (2.14 to 14.13) for CVD deaths. There was no association between perceived control and mortality in Russia; the adjusted HRs for all-cause mortality were 1.03 (0.79 to 1.34) in men and 1.29 (0.82 to 2.02) in women. CONCLUSIONS: Low perceived control was associated with increased risk of all-cause and CVD mortality in Czech and Polish cohorts but not in Russia. It is possible that this inconsistency may partly reflect a different sociocultural understanding of the concept of control in Russia.
Keywords: senioři; proporcionální rizikové modely; Poland; Proportional Hazards Models; Russia; MORTALITY; chování snižující riziko; Czechoslovakia; Rusko; Middle Aged; průzkumy a dotazníky; Československo; mužské pohlaví; příčina smrti; Prospective Studies; Risk Reduction Behavior; Polsko; Health Knowledge, Attitudes, Practice; Cardiovascular disease; Cardiovascular Diseases; městské obyvatelstvo; ženské pohlaví; Humans; prospektivní studie; Surveys and Questionnaires; lidé středního věku; EASTERN EUROPE; PSYCHOSOCIAL FACTORS; zdraví - znalosti, postoje, praxe; Urban Population; Female; Aged; Cause of Death; kardiovaskulární nemoci; lidé; Male